An electrical power system for CubeSats - Sheard, Benjamin Charles De Villiers (Department of Electrical Engineering, 2016)
The advent of CubeSats has provided a platform for relatively low-budget programmes to realise space missions. In South Africa, Stellenbosch University and the Cape Peninsula University of Technology have impressive space programmes and have been involved in numerous successful satellite launches. A number of CubeSat projects are currently in progress and commercial-grade Attitude Determination and Control Systems (ADCS), and communications modules, are being developed by the respective universities. The development of a CubeSat-compatible Electrical Power System remains absent, and would be beneficial to future satellite activity here in South Africa. In this thesis, some fundamental aspects of electronic design for space applications is looked at, including but not limited to radiation effects on MOSFET devices; this poses one of the greatest challenges to space-based power systems. To this extent, the different radiation-induced effects and their implications are looked at, and mitigation strategies are discussed. A review of current commercial modules is performed and their design and performance evaluated. A few shortcomings of current systems are noted and corresponding design changes are suggested; in some instances these changes add complexity, but they are shown to introduce appreciable system reliability. A single Li-Ion cell configuration is proposed that uses a 3.7 V nominal bus voltage. Individual battery charge regulation introduces minor inefficiencies, but allows isolation of cells from the pack in the case of cell failure or degradation. A further advantage is the possibility for multiple energy storage media on the same power bus, allowing for EPS-related technology demonstrations, with an assurance of minimum system capabilities. The design of each subsystem is discussed and its respective failure modes identified. A limited number of single points of failure are noted and the mitigation strategies taken are discussed. An initial hardware prototype is developed that is used to test and characterise system performance. Although a few minor modifications are needed, the overall system is shown to function as designed and the concepts used are proven.